3D printing highly stretchable conductors for flexible electronics with low signal hysteresis. Issue 1 (2nd January 2022) - Zhou, Jun; Yan, Honghao; Wang, Chengyun; Gong, Huaqiang; Nie, Qiuxiao; Long, Yu
ABSTRACT: Previous studies on UV-curable elastomer for digital light processing (DLP) 3D printing flexible electronics mostly focused on higher stretchability and healability, thereby ignoring rapid recoverability after a stretch which is very important for the real-time transmission of electrical signals in flexible electronics. Herein, a UV-curable elastomer is developed with a novel dynamic hierarchical crosslinking network that can be stretched up to over 800% and rapid recoverability at 300% strain. We proposed a hydrogel-elastomer assembling process to simplify the manufacturing process for stretchable conductors. The stretchable conductors served as a strain sensor exhibiting excellent stability and repeatability after 10 cycles at 20–50% strain with low signal drift and hysteresis, Moreover, the strain sensor can be utilised in recognising the different bending angles of the finger, making DLP printing of conductive elastomer a viable strategy for the rapid manufacturing of flexible electronics.